1997
DOI: 10.1111/j.1349-7006.1997.tb00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor‐β and Hepatocyte Growth Factor Produced by Gastric Fibroblasts Stimulate the Invasiveness of Scirrhous Gastric Cancer Cells

Abstract: Scirrhous gastric carcinoma is characterized by cancer cells that infiltrate rapidly in the stroma with extensive growth of fibroblasts. In the present study, we examined the effect of gastric fibroblasts on the invasiveness of a Scirrhous gastric cancer cell line, OCUM‐2D, using an invasion assay. Gastric fibroblast‐derived conditioned medium (CM) significantly stimulated the invasiveness of OCUM‐2D cells, as did transforming growth factor‐β (TGF‐β) and hepatocyte growth factor (HGF). The stimulating activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 30 publications
0
62
1
Order By: Relevance
“…TGFβ produced from fibroblasts increases the invasiveness of scirrhous gastric cancer cells [24]. TGFβ is detected in a latent form in the conditioned medium from fibroblasts and in an active form in the conditioned medium from gastric cancer cells [18,24]. The latent TGFβ is activated by proteases such as plasmin and cathepsin [25].…”
Section: Migration-stimulating Activity Of Gastric Cancer Cells By Fimentioning
confidence: 99%
“…TGFβ produced from fibroblasts increases the invasiveness of scirrhous gastric cancer cells [24]. TGFβ is detected in a latent form in the conditioned medium from fibroblasts and in an active form in the conditioned medium from gastric cancer cells [18,24]. The latent TGFβ is activated by proteases such as plasmin and cathepsin [25].…”
Section: Migration-stimulating Activity Of Gastric Cancer Cells By Fimentioning
confidence: 99%
“…19,20 In vitro studies have demonstrated that HGF stimulates invasion or proliferation of gastric cancer cells. 20,21 Furthermore, HGF affects the morphology of mesothelial cells, such that they become prone to peritoneal dissemination of cancer cells. 22 Recently, a small molecular c-Met inhibitor, SU11274, has been developed and shown to inhibit c-Met phosphorylation and c-Met-dependent cell motility, invasion and proliferation in vitro.…”
mentioning
confidence: 99%
“…Accumulating evidence has shown that HGF plays a distinct role in tumour-stromal interactions (Seslar et al, 1993;Rosen et al, 1994;Matsumoto et al, 1996;Inoue et al, 1997;Nakamura et al, 1997;Jiang et al, 1999). HGF has potent motogenic activity on various types of carcinoma cells, leading to the dissociation, scattering and migration of cells (Weidner et al, 1990;Jiang et al, 1993Jiang et al, , 1999Matsumoto et al, 1994Matsumoto et al, , 1996Jeffers et al, 1996;Rosen et al, 1996;Inoue et al, 1997;Nakamura et al, 1997).…”
mentioning
confidence: 99%